Determination of the Band Gap and Intensity of Palladium/Silver Doped TiO2 Nano Particles Using Diffuse Reflectance and Photoluminescence Spectra - K.I., Omoniyi; A.O., Aroh; C.E., Gimba; H., Abba; M.T., Yilleng (Journal of Science and Technology, 2018)
The photocatalysts Pd/TiO2, Ag/TiO2 and Ag/Pd-TiO2 were prepared using the sol immobilization method. The photocatalysts were characterized by the use of diffuse reflectance spectra (DRS) and photoluminescence spectra. Analysis of Ag/TiO2 and Ag/Pd -TiO2 using diffuse reflectance spectra (DRS) indicated reduction of band gap energy from 3.2 eV to 2.7 eV for Ag/Pd-TiO2 which makes it possible for the use of sunlight as excitation energy. Photo luminescence spectra analysis carried out on the dopants of Ag/TiO2, Pd/TiO2 and Ag/Pd-TiO2 measured the intensity which gives the rate of recombination of photo-generated electron-hole pairs in TiO2. The result indicated that reduction in intensity was highest for the co-doped Ag/Pd-TiO2. This accounts for its increase in photo catalytic property. Therefore, modification of TiO2 with Ag and Pd will provide the platform for its enhanced photocatalytic performance relevant in environmental science.